2005
DOI: 10.1016/j.chemgeo.2004.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and oxygen isotopic record in sulfate and sulfide minerals of early, deep, pre-Main Stage porphyry Cu–Mo and late Main Stage base-metal mineral deposits, Butte district, Montana

Abstract: Typical porphyry-type Cu-Mo mineralization occupies two connected domal centers, the eastern Pittsmont and western Anaconda domes, that predate and largely underlie the well-known, throughgoing, Main Stage polymetallic veins of Butte. Among the sulfur-bearing minerals recovered from deep drill core of this early pre-Main Stage hydrothermal assemblage are anhydrite, chalcopyrite, pyrite, and molybdenite in veinlets bordered by K-silicate alteration, and pyrite from slightly younger quartz-pyrite veinlets with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 54 publications
(101 reference statements)
9
39
0
Order By: Relevance
“…Data from El Salvador, Chile (Field and Gustafson 1976), Gaspé, Quebec (Shelton and Rye 1982), Papua New Guinea (Eastoe 1983), and Butte, Montana (Field et al 2005) are plotted in Figure 16. In general, the paired data plotted in Figure 16 suggest that equilibrium conditions were approximated by these hydrothermal systems.…”
Section: Porphyry and Epithermal Depositsmentioning
confidence: 99%
“…Data from El Salvador, Chile (Field and Gustafson 1976), Gaspé, Quebec (Shelton and Rye 1982), Papua New Guinea (Eastoe 1983), and Butte, Montana (Field et al 2005) are plotted in Figure 16. In general, the paired data plotted in Figure 16 suggest that equilibrium conditions were approximated by these hydrothermal systems.…”
Section: Porphyry and Epithermal Depositsmentioning
confidence: 99%
“…Nor could the H 2 S have been generated abiotically by dissolution of hydrothermal sulfide minerals such as ZnS under anaerobic, initially acidic conditions, as this process would have produced H 2 S with an isotopic composition similar to that of the precursor sulfide minerals. Published values for d 34 S of pyrite and other sulfide minerals from the Butte ore bodies were recently compiled and discussed by Field et al (2005). These data, summarized in Fig.…”
Section: Origin Of Sulfide and Sulfatementioning
confidence: 99%
“…A detailed discussion about sulfur isotopic fractionation at magmatic to hydrothermal conditions is beyond the scope of this study, but can be found in the literature (e.g., Field and Gustafson, 1976;Ohmoto and Rye, 1979;Hoefs, 1987;Ishihara and Sasaki, 1989;Rollinson, 1993;Ohmoto and Goldhaber, 1997;Field et al, 2005;Li and Liu, 2006). However, it is noted that sulfate species tend to be enriched in 34 S relative to sulfide species at magmatic temperatures.…”
Section: Discussionmentioning
confidence: 93%
“…T, pH (Field and Gustafson, 1976;Sakai et al, 1982Sakai et al, , 1984Ueda and Sakai, 1984;Zheng, 1990;Poulson et al, 1991;Alt et al, 1993;Ohmoto and Goldhaber, 1997;de Hoog et al, 2001;Ripley and Li, 2003;Field et al, 2005). This helps the establishment of genetic models for mineral deposits, which bears implications for mineral exploration.…”
mentioning
confidence: 99%